The Relationship Between Addiction to the Online Game Mobile Legends Bang-Bang (MLBB) and Sleep Quality in Teenagers - Fauzi, Ferdi; Rusli, Devi (Jurnal Psikologi Teori dan Terapan, 2024)
Background: Teenagers in Padang City have a high interest in online games, especially Mobile Legends Bang-Bang. Objective: The aim of research was to determine the relationship between online game addiction and sleep quality in teenagers of Padang. Method: A correlational quantitative approach was used for this research. The sample used 300 teenagers using purposive sampling technique. The sleep quality measuring tool by Buysse et.al (1989) contains 10 items consisting of 18 subjective questions and 6 observational questions. The online game addiction measuring tool contains 21 items with 3 questions for each aspect. Data analysis used Spearman’s technique because the data distribution was not normal but linear for both variables. Result: The results show a significant relationship between online game addiction and sleep quality in teenagers, with p = 0.001 (< 0.05). Conclusion: Thus, it can be concluded that the higher the level of online game addiction in teenagers, the lower the sleep quality they experience. This research also found differences in the level of online game addiction and sleep quality in terms of gender.Abstrak Latar Belakang: Remaja di Kota Padang memiliki minat yang tinggi pada game online khususnya Mobile Legends Bang-Bang. Tujuan: Tujuan penelitian dilakukan adalah mengetahui hubungan  kecanduan game online dengan sleep quality pada remaja di Kota Padang. Metode: Pendekatan kuantitatif korelasional digunakan untuk penelitian ini. Sampel digunakan sebanyak 300 remaja melalui teknik purposive sampling. Alat ukur sleep quality oleh Buysse et.al (1989) terdapat 10 item terdiri 18 pertanyaan subjektif dan 6 pertanyaan observatif.  Alat ukur kecanduan game online memiliki 21 item dengan 3 pertanyaan pada tiap aspek. Analisis data menggunakan teknik Spearman karena distribusi data tidak normal tetapi linier pada kedua variabel. Hasil: Hasil menunjukkan adanya hubungan signifikan antara kecanduan game online dan sleep quality pada remaja, dengan nilai p=0,001 (< 0,05). Kesimpulan: Dengan demikian, dapat disimpulkan bahwa makin tinggi tingkat kecanduan game online pada remaja, maka makin rendah sleep quality yang mereka alami. Penelitian ini juga menemukan adanya perbedaan tingkat kecanduan game online dan sleep quality yang ditinjau dari jenis kelamin.